Stratigraphy and geologic evolution of the Cañadón Asfalto Basin, Chubut Province, Argentine (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Cañadón Asfalto Basin, situated in central Patagonia between the North Patagonian Massif and the Golfo San Jorge Basin (Fig. 1), comprises a thick column of Jurassic and Cretaceous sediments accumulated in several depocenters separated by transference zones of basement blocks, namely the Gastre, Gan Gan, Fossatti, Valle de General Racedo, Gorro Frigio and Paso de Indios depocenters (Figs. 2-4). They were included in a major rift zone that later evolved in a complex way with several deformation phases. Sediments were grouped into three megasequences (J1, J2, and K) separated by regional unconformities (Fig.5), overlying a Paleozoic basement, composed of schists and granitoids. The J1 Megasequence (Hettangian-Sinemurian?/Pliensbachian to late Bajocian) is composed of the Las Leoneras Formation, the Lonco Trapial Formation and the Cañadón Asfalto Formation (Figs. 6, 7). The two latter were classicaly considered of Middle to Late Jurassic age but new interpretations indicate these thick sedimentary-volcanic succesions are older (Early to Middle Jurassic), and were accumulated in a relatively short period of time. The passage between units is regarded as transitional in spite of the fact that they are locally separated by erosive or angular unconformities. These discontinuities are typical of high-relief volcanic environments and therefore they lack regional significance. The rift evolved from incipient to juvenile during the sedimentation of the J1 Megasequence. Sedimentation took place in continental environments (fluvial, lacustrine and volcanic) with high volcaniclastic input. The wet, temperate/warm climate favoured a high biodiversity. The black shales of the Cañadón Asfalto Formation represent the Toarcian anoxic global event.The J2 Megasequence (Figs. 8-12) comprises the thick succesion of alluvial and lacustrine sediments of the Cañadón Calcáreo Formation (Oxfordian-Kimmeridgian), which is separated by an angular unconformity from the Cañadón Asfalto Formation. These Late Jurassic sediments were accommodated in small half-grabens limited by uplifted mountain blocks, in a basin-and-rangelike landscape, separated by transference areas, synchronically with a tectonic reactivation of the rift. The J2 Megasequence is partially equivalent to the Anticlinal Aguada Bandera Formation in the Golfo de San Jorge Basin. The warm/temperate climate with dry periods allowed the development of a diverse biota with a rich palynological association in fish-bearing black shales. These shales are overlain by a progradational fluvio-deltaic succession, swiftly accumulated in a short period of time (about 1 Ma), which was partially or totally eroded previously to the Chubut Group sedimentation. From the Tithonian until the Hauterivian an important stratigraphic gap exists. Initillay a regional tectonism took place, related to a dextral shear system that uplifted large areas into the basin. Partial block rotation in a transpressive-transtensive regime controlled by old tectonic lineaments occurred, although the mechanisms of uplifting are not definitely established. The northwest-oriented master faults of the original rift were inverted and sedimentation in the basin almost ceased. This is the most significant tectonic event in the basin and it is recorded by an angular unconformity that separates the Grupo Chubut from the older units. Facies and thickness changes in the basal units of the K Megasequence suggest accomodation space formation at the end of this stage was controlled by active faulting. The K Megasequence (Figs. 13, 14) includes the terrestrial beds of the Chubut Group deposited in Barremian-Campanian times, as well as the shallow-marine deposits of the Paso del Sapo and Lefipán Formations (Campanian-Danian), which represent the first Atlantic transgression into the basin. Both units are separated by a slightly angular unconformity that points to some local tectonism in the Late Cretaceous. The mountain systems collapsed and the basin expanded with a typical sag style because of the slow dissipation of the termal anomaly of the rift, giving place to the accumulation of thick continental sediments of the Chubut Group unconformably overlying all the older units and also the basement. The NW-SE-oriented faults were not anymore the main control in the basin configuration and they were totally or partially replaced by E-W faults, already present in the original grain of the basement. North-south extension, ortogonal to the Pacific subduction margin, took place during this period. Contractional deformation occurred in the western area of the basin during the PaleoceneEocene and subsidence ceased in the remaining of the basin. This indicates an “old” back-arc compressive deformation represented in the Cañadón Asfalto Basin by the Complejo Volcánico y Piroclástico del Río Chubut Medio, accumulated in caldera settings. Tectonic inversion (Fig. 15) and generalized uplift took place in Oligocene?-Miocene to Recent times, represented by local folding of high variable style and intensity, and generalized faulting of the rocks, represented by several fault systems. Some of the Mesozoic depocenters were totally exposed, whereas others remained partially buried and new Miocene depocenters were formed. The Sierra de Traquetrén was uplifted during this period, along an extensive, NW-SE-oriented fault, that was the former limit of an extensional depocenter. Uplifting was contemporaneous to the formation of the Sierra de San Bernardo in the Golfo de San Jorge basin, located to the southeast of the basin reported in this contribution.
Keywords: Cañadón Asfalto Basin, Chubut, Argentina, Geology, Stratigraphy, Sedimentology, Geological evolution.